2019
DOI: 10.1039/c8ra09894h
|View full text |Cite
|
Sign up to set email alerts
|

A UPLC-MS-based metabolomics approach to reveal the attenuation mechanism of Caowu compatibility with Yunnan Baiyao

Abstract: Yunnan Baiyao (YNBY) is a well-known traditional Chinese medicine containing Caowu (Aconiti kusnezoffii radix, CW). However, the application of YNBY is limited by the toxicity of CW. Notably, CW is not used alone in YNBY, but is combined with other herbs in a formula for clinical use. In the present study, the compatibility of the protective effects and mechanism of YNBY with the potential toxicity of CW was investigated. After combining with other compatible herbs, the serum metabolic disorder induced by CW c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Our data show that SIM could sharply down-regulate the hepatic GCDCA level, indicating a beneficial effect against the hepatotoxicity of GCDCA. TDCA is a main bioactive substance in animal BAs that is found to have the potential of anti-inflammatory activity (Ren et al, 2019). Prior investigation reported that TDCA might significantly inhibit acute myocardial infarction and chronic inflammation by activating protease cascades to induce apoptosis (Mao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that SIM could sharply down-regulate the hepatic GCDCA level, indicating a beneficial effect against the hepatotoxicity of GCDCA. TDCA is a main bioactive substance in animal BAs that is found to have the potential of anti-inflammatory activity (Ren et al, 2019). Prior investigation reported that TDCA might significantly inhibit acute myocardial infarction and chronic inflammation by activating protease cascades to induce apoptosis (Mao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers have become an integral part of the research on diseases. [54][55][56][57][58][59] In this study, it was found that PF regulated 10 biomarkers by the metabolic pathways of phenylalanine, tyrosine and tryptophan biosynthesis, phenylalanine metabolism, and tryptophan metabolism, to achieve a certain therapeutic effect. Although the systematic metabolic analysis was used in our study, we can integrate the physiological indicators and pathological observations to improve this study.…”
Section: Discussionmentioning
confidence: 84%
“…Ren et al performed MS-based metabolomics to study the toxic effects of Yunnan Baiyao on normal rats. 86 According to the results of the study, the toxicity of Aconiti kusnezoffii radix was observed earlier than in histopathology. Moreover, by comparing the changes in metabolite callback under the action of Aconiti kusnezoffii radix, processed Aconiti kusnezoffii radix, Yunnan Baiyao and Yunnan Baiyao lacking Aconiti kusnezoffii radix, with a secondary focus on metabolic pathways, the key metabolic pathways that may play a role in attenuation were determined.…”
Section: Application Of Ms-based Metabolomics In Medical Sciencementioning
confidence: 89%